PENANAMAN NILAI ADIWIYATA DALAM PEMBELAJARAN PAI MI (Studi Multi Situs di MIN 1 Palembang dan MIN 2 Palembang) - Faisal Faisal; Tutut Handayani; Fuaddillah Ali Sofyan (Universitas Muhammadiyah Ponorogo, 2019)
Related to the government's efforts to implement the Education Policy Environment, namely by launching the Adiwiyata Program for schools, then MIN 1 and MIN 2 Palembang make Adiwiyata a target to measure efforts made by the school in achieving its mission as a cultured school living environment. This is because through the adiwiyata program there are clear indicators can be used to measure the efforts made, besides also getting used to The school properly documents all activities and programs held. Qualitative research approach with multi-site research types. The technique of collecting data is by observation, interviews and documentation. While. Data analysis techniques use data reduction, presentation and conclusion. The research results are: 1) Adiwiyata value at MIN 1 Palembang Example and MIN 2 Palembang model, namely respect for nature, responsibility, compassion and concern for nature, Gratitude, and Brotherhood among fellow Muslims. 2) The cultivation of adiwiyata values in the learning of MI Islamic Education is carried out in a way learning in class through material Fiqh, Akhah Akhlak, Qurdits, and SKI. The learning uses the method of direct application and also through the media infoccus. This makes it easier for teachers to instill adiwiyata values on PAI MI learning. 3) Supporting and inhibiting factors for planting adiwiyata values in PAI learning. The supporting factor is the principal's policy requires the teacher to provide insight and advice about the environment, the existence of work the same as outside parties in optimizing the adiwiyata program, coordination and loyal collaboration between the employee, teacher, student and second stakeholder of the MIN. The inhibiting factors are infrastructure and funding.